Coccygectomy a novel and definitive approach to surgical treatment of a tailgut cyst - Lindsey Ross; E.D. Adams; A. Parrish; J. Zhai; M. Chithriki; D. Magner; P.J. Johnson (Interdisciplinary Neurosurgery, 2021)
Coccygectomy is a simple and safe procedure often used to treat coccydynia. Here we describe this unique approach to access a rare case of tailgut cyst presenting as a phlegmonous pelvic mass fistulized to the sacrum and multiple pelvic organs and complicated by pelvic actinomycosis.